Multiscale characterization of medical devices and pharmaceutical formulations with 3D X-ray microscopy and computed tomography - Herminso Villarraga-Gómez; Ria L. Mitchell (e-Journal of Nondestructive Testing)
Effective healthcare relies on safe and reliable drug delivery systems that enhance cure rates while minimizing side effects and ensuring ease of use for better patient compliance. This requires advanced biomedical engineering approaches, utilizing various dosing forms such as solids (e.g., tablets), powders (e.g., capsules), liquids (e.g., injections and emulsions), and gases (e.g., aerosols and atomizers or inhalers). It also requires improving the medicinal properties of drug formulations for maintaining effective drug concentration at target body sites over time. Public acceptance of drugs and medical products depends on approval from regulatory agencies, ensuring quality and performance. Manufacturers must follow regulatory frameworks that encompass pharmaceutical research, manufacturing, and quality assurance (QA). Quality control (QC) guarantees that products are safe and effective. However, inspecting medical devices and pharmaceutical compounds, especially their interior, is challenging with traditional measurement systems, making X-ray imaging a valuable non-destructive method for examining their internal structures. This paper discusses advancements in 3D X-ray imaging workflows for characterizing medical devices and pharmaceutical formulations. It also covers deep-learning (DL) data reconstruction techniques that enhance 3D X-ray microscopy (XRM) and computed tomography (CT) applications in drug delivery and the pharmaceutical industry. Correlative workflows combining CT and 3D XRM can operate independently or alongside other microscopy methods, such as scanning electron microscopy (SEM), providing comprehensive characterization across multiple length scales, from centimeter-range features in medical devices to features such as pores, cracks, and coatings within pharmaceutical formulations ranging from several hundreds of micrometers to tens of nanometers in scale.